Hazard Risk Assessment in Post Weld Heat Treatment Process Using the Fine-Kinney Method - Sianturi, Gabriel; Fiatno, Aris; Henny, Henny; Syafei, M.Yani; Hakim, M.Difa Aldira (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
Hazards in the workplace are sources that have the potential to cause work accidents that can harm workers, therefore it is important to carry out a hazard risk assessment as an effort to eliminate or reduce the risk of hazards in the workplace to protect workers. The purpose of this study is to asses the risk of hazards of Post Weld Heat Treatment (PWHT) process for pipes in a manufacturing company through identification of potential hazards, risks analysis and evaluation to determine control measures. Hazards identification in the PWHT work revealed there are 34 hazards that have the potential to cause work accidents. Hazard risk analysis using Fine-Kinney method shows the hazard risk levels in the PWHT work is from low to high, with a low level risk percentage of 23.5%, a possible risk level of 20.6%, a substantial risk level of 47.1% and a high risk level of 8.8%. The proposed control measures for eliminating or reducing the risk of hazard in each task is carried out by hierarchy of controls through the elimination, substitution, engineering controls, administrative controls and personal protective equipment.